Tumor-associated B cells and humoral immune response in head and neck squamous cell carcinoma. (4th March 2019) - Lechner, Axel; Schlößer, Hans A.; Thelen, Martin; Wennhold, Kerstin; Rothschild, Sacha I.; Gilles, Ramona; Quaas, Alexander; Siefer, Oliver G.; Huebbers, Christian U.; Cukuroglu, Engin; Göke, Jonathan; Hillmer, Axel; et al.
ABSTRACT: B lymphocytes are important players in immune responses to cancer. However, their composition and function in head and neck squamous cell carcinoma (HNSCC) has not been well described. Here, we analyzed B cell subsets in HNSCC (n = 38), non-cancerous mucosa (n = 14) and peripheral blood from HNSCC patients (n = 38) and healthy controls (n = 20) by flow cytometry. Intratumoral B cells contained high percentages of activated (CD86 + ), antigen-presenting (CD86 + /CD21 − ) and memory B cells (IgD − /CD27 + ). T follicular helper cells (CD4 + /CXCR5 + /CD45RA − /CCR7 − ) as key components of tertiary lymphoid structures and plasma cells made up high percentages of the lymphocyte infiltrate. Percentages of regulatory B cell varied depending on the regulatory phenotype. Analysis of humoral immune responses against 23 tumor-associated antigens (TAA) showed reactivity against at least one antigen in 56% of HNSCC patients. Reactivity was less frequent in human papillomavirus associated (HPV + ) patients and healthy controls compared to HPV negative (HPV − ) HNSCC. Likewise, patients with early stage HNSCC or MHC-I loss on tumor cells had low TAA responses. Patients with TAA responses showed CD4 + dominated T cell infiltration compared to mainly CD8 + T cells in tumors without detected TAA response. To summarize, our data demonstrates different immune infiltration patterns in relation to serological TAA response detection and the presence of B cell subpopulations in HNSCC that can engage in tumor promoting and antitumor activity. In view of increasing use of immunotherapeutic approaches, it will be important to include B cells into comprehensive phenotypic and functional analyses of tumor-associated lymphocytes.